Relapse of Non-Hodgkin's Lymphoma Involving the Trachea: Acute Subglottic Obstruction. (4th March 2014) - Wang, Allen Y.; Wang, Jeffrey T.; Shen, Yi; Levin, Brett
Abstract : Relapsing lymphoma involving the trachea causing tracheal obstruction is exceedingly uncommon. Despite its rarity, it should be considered in the differential diagnosis when a patient with known lymphoma presents with signs of airway obstruction such as stridor. We report an unusual case of relapsing non-Hodgkin's lymphoma with tracheal involvement in a 57-year-old female and review the relevant literature. It is highly unusual for relapsing lymphoma to involve the trachea causing tracheal obstruction. Despite its rarity, it can present with life-threatening airway obstruction which may be rapidly progressive requiring immediate surgical intervention such as tracheostomy.